Utilization of bintaro shells as activated carbon to reduce phosphate in laundry wastewater - Martogi - Pasaribu (Journal of Environmental Engineering and Waste Management, 2020)
Laundry wastewater is dangerous if it is immediately disposed into a river without treating it first. One of the chemicals contained in laundry wastewater is a phosphate compound. If laundry wastewater is discharged directly into the river it will increase the phosphate content as a nutrient in river water which can be dangerous for living creatures. The high nutrient in the river will cause eutrophication in the river which will adversely affect aquatic biota. One treatment that can be done is the process of adsorption with activated carbon made from bintaro fruit shells.